PENGARUH PENGETAHUAN DAN PERSEPSI TERHADAP PEMANFAATAN PELAYANAN DETEKSI DINI KANKER SERVIKS DI PUSKESMAS TIGA BINAGA KABUPATEN KABANJAHE - ASTARIA Br GINTING (JURNAL ILMIAH SIMANTEK, 2019)
Cervical cancer is the second type of cancer after breast cancer that is most commonly suffered by women. Tiga Binaga Puskesmas is one of the Puskesmas with the use of Cervical Cancer Early Detection services not optimal in Kabanjahe District. Achievement of coverage of 11.8% in 2013, while the target to be achieved is 80%. This study aims to analyze the effect of Knowledge, and Perception on the use of cervical cancer early detection services at the Tiga Binaga Health Center. This type of research is Cross-Sectional Study with an explanatory approach. The research was conducted from March to May 2017. The population was all women of reproductive age (WUS) totaling 1,995 people and a sample of 65 people. Data obtained by interview using a questionnaire, analyzed by logistic regression in testing α = 0.05.The results showed that statistically Knowledge, and Perception had a significant effect on the utilization of early cervical cancer detection services in Tiga Binaga Health Center, Kabanjahe District. Knowledge variable is the variable that has the most influence on utilization. It is recommended to the Tiga Binaga Community Health Center: (a) seek to increase knowledge about early detection of cervical cancer by health workers to mothers through counseling both formal and informal activities by adjusting language that is easily understood by the local population, (b) seeking to increase maternal affordability for services early detection of cervical cancer regularly through the activation of services at sub-health centers, and health centers.